Sustainable concretes – through reducing the water absorptivity to improved durability - Figmig, Róbert; Eštoková, Adriana; Smoláková, Michaela (International Conference “Environmental Engineering”, 2017)
Water absorptivity (WA) is one of the crucial parameters affecting the penetration of aggressive ions when concrete material is exposed to an aggressive environment and is closely linked with a depth of penetration of water under pressure into the concrete. Concrete used for prefabricated elements and structures as cesspits, manholes, pipe lines or parts of the wastewater treatment plants, has to meet a requirement for maximum water absorptivity of 6.0 wt. % in accordance with national and international standards. The article deals with a study of concretes’ water absorptivity of the precast products for environmental purpose, where the exposure class XA (chemical attack) is required. The research is focused on reducing WA by using various modification of standard mix design (Portland cement, water, fine and coarse aggregate, plasticizer), e.g. by using different cement types, cementous supplementary additives, admixtures, finest aggregate particles or by reducing water/binder ratio. The concretes of various mix design modifications were compared with a reference concrete in relation to the standard. The economical and environmental aspects were also taken into consideration.
Keywords: concrete technology; materials; water absorption; durability